Whole genome sequence-based genetic characterization of Muturu, an endangered trypanotolerant population of West African Bos Taurus - Tijjani, A.; Utsunomiya, Yuri Tani; Oyekanmi Nash, O.; Hanotte, Olivier H. (2019)
Muturu cattle, mostly found nowadays in Nigeria, have been classified as an endangered cattle population due to the rapid decline in their population size. They are among the shorthorn West African B. taurus trypanotolerance cattle. Here, we report candidate signature of positive selection obtained from whole genome re-sequencing data in a population of 10 Muturu samples from southeastern Nigeria. We present within Muturu population results in comparison with other B. taurus cattle including the trypanotolerant longhorn N’Dama and the European Holstein and Jersey dairy cattle. We identify a total of 8,937,932 single nucleotide polymorphisms (SNPs) and 1,373,437 insertion/deletions (indels) on the autosomes, of which about 11.3% and 10.2% respectively, are unique to Muturu. As revealed by the integrated haplotype score (iHS) test, 266 loci and 432 related candidate genes are under positive selection in the Muturu genome. One of the most significant regions is located on BTA 23. It includes several genes belonging to the major histocompatibility complex (MHC) with functions related to both innate and adaptive immunity. Thirty-one candidate genes including the MHC genes region were also found under selection in N'Dama. Several genes such as KIT, ZRANB3, MAP3K5, ABCGR, GHR, LAP3, SRY, RFX2, GPX5 and PRKAG3 which are related to coat colour, feed efficiency, milk production, reproduction and response to heat stress were also identified. Our results provide insights into the candidate genes under selection in Muturu paving the way for further investigations into important adaptation traits such as trypanotolerance in West African B. taurus.